Healthy Teen School: Gerakan Gizi Seimbang Dan Jajanan Sehat Pada Siswa SMP Negeri 19 Medan - Tifani Hadi Tri Wahyuni; Marta Imelda Br. Sianturi; Asima Lamtiar Hotnauli Pakpahan; Nurhayani Harahap; Amanda Sheira Silitonga; Yumiati Mbang Kahi (STIKES Columbia Asia Medan, 2026)
Adolescents are a nutritionally vulnerable group at risk of double burden of malnutrition. Riskesdas 2023 data showed that the prevalence of undernutrition in adolescents aged 13–15 years in North Sumatra reached 16.8%, while overweight and obesity reached 18.3%. The habit of consuming unhealthy snacks at school is one of the main preventable risk factors through structured nutrition education. Objective: This community service program aimed to increase knowledge of balanced nutrition and healthy snack selection behavior among Grade VIII students of SMP Negeri 19 Medan. Methods: Activities were carried out through interactive lectures, demonstrations, educational games, and workshops with 64 students. Evaluation used pre-test and post-test analysis with Wilcoxon Signed Rank Test. Results: There was a significant increase in nutritional knowledge in both classes (p=0.001) and healthy snack selection behavior (p=0.000). Conclusion: The Healthy Teen School program effectively improved adolescent nutrition knowledge and behavior.